A macro-model to monetary transmission analysis in Tunisia - Aymen Makni (Graduate Institute of International and Development Studies, 2019)
In this paper, we develop a gap model based on a reduced form of the New Keynesian Model. The model offers various scenario structure tools which analyze the dynamics of key macro economic variables under diverse shocks and depicts their properties and historical decompositions. This framework rationalizes the monetary transmission mechanism as well as the effects of major shocks influencing the macroeconomic variables and can assess the role of monetary policy in reacting to observed and anticipated changes in inflation and other economic variables. This model provides a useful framework detailing monetary policy and helping policymakers mainly to react strongly to inflation.
Keywords: E52; E58; E10; E50; 330; Monetary Policy; Central Banks and Their Policies; Macroeconomic Model; Monetary Transmission Mechanism